Strategi Meningkatkan Minat Wisatawan Untuk Berkunjung Ulang ke Destinasi Desa Wisata Melalui Peningkatan Daya Tarik - Fahimah, Mar'atul; Qomariyah, Siti Nur; Dewantara, Rahmat Maulana Sukma (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2023)
Sumber Gempong Tourism is located in one of the villages of Mojokerto district. This destination is in the Ketapanrame tourist village area, which has beautiful natural views. Visitors can enjoy the beauty of nature and the surrounding environment from views of mountains, rice fields, forests, rivers, water sources and facilities. This study aims to find out how attractiveness influences interest in revisiting the Sumber Gempong Trawas rice field tourism. The associative approach in research focuses on looking for relationships or associations between variables. The population of this study includes all people who have visited the Sawah Sumber Gempong tourist destination in Trawas and have visited it at least once. The number of samples was 100 visitors. The sampling technique is purposive sampling. In research using multiple regression analysis. The results show that the attractiveness variable influences visitors' desire to visit the Sumber Gempong Trawas Mojokerto.